SYNTACTICAL ERRORS IN SHORT STORIES COMPILATION BOOK WRITTEN BY ENGLISH DEPARTMENT STUDENTS OF DARUL ULUM ISLAMIC UNIVERSITY OF LAMONGAN - Leli Dwi Saputri; Irmayani Irmayani (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2017)
Writing is a process of communicating the writer’s idea to the reader in a written form. According to Leo (2007:1) writing as a process of expressing ideas or thought in words should be done at our leisure. Writing has many different kinds, such as: novels, short stories, reports, letters, essays, poems, etc. All of them are quite different. But all of them are writing. In this research, the researcher wants to find out types of students’ syntactical Error in writing short story of English Department student and the causes of error in short story compilation book of English department student .This study uses a qualitative design in which the data are taken from the sentences of short stories in the form of book. There are twelve short stories as the data of this study. The data are collected and analyzed using Ellis’ error analysis theory. Those are identifying error, describing error, explaining error and evaluating error. The analysis found that there are 560 errors. it was divided into four types of syntactical errors which were used; they are Omission 137, Addition 64, Misformation 343 and Misordering 16. From all errors found, most of them were caused by intralingual error (Error within the target language). It takes 491 occurrences. And the rest of them were caused by interlingual error (Mother tongue interference). It took 69 occurrences. From all of errors which found in the students’ short stories were dominated by local error. It was found about 245 errors of 325 of sentence errors. Then the rest of them were global error. It took 80 times. The percentage of errors in the short story was not more than 25% of each short story. Therefore, it can be concluded the most dominant type of syntactical errors in short story compilation book of English Department student was misinformation. Most of the errors found were caused by intralingual error (error within the target language). The errors found were categorized as local error and few of it were global error. The students’ short stories or writing were good in which the percentage of errors was not more than 25% of each short story. It is hoped that the result of this study will be useful to everyone who wants to study about syntactical error.